Praktik Budi Daya Pemicu Perkembangan Busuk Batang Jeruk di Kabupaten Bangli - Widyastiti, I Gusti Ayu; Widodo, Widodo (Jurnal Fitopatologi Indonesia, 2021)
Cultural Practices Triggering the Development of Citrus Stem Rot in District of BangliBangli-Province of Bali is one of central areas of citrus production in Indonesia. Stem rot disease caused by Lasiodiplodia theobromae is one of the important constraints that can reduce the production of citrus in Indonesia. The aim of this study was to determine the factors contribute to citrus stem rot disease development in Bangli District-Province of Bali. Observation of the disease condition and in-depht interview related with citrus cultural practices undertaken by farmers was conducted on 50 plots. To determine the association between cultural practices and disease severity was performed by using correspondence and contingency (chi square) analysis. In this study, we determined 4 factors of cultural practices and 1 plant factor that were related and have a significant effect on the severity of citrus stem rot. These factors were the frequency of mechanical weeding, plant population per hectare, herbicide application, dosage of nitrogen fertilizer, and plant age.